2020
DOI: 10.1038/s42003-020-01219-2
|View full text |Cite
|
Sign up to set email alerts
|

Reg4 and complement factor D prevent the overgrowth of E. coli in the mouse gut

Abstract: The expansion of Enterobacteriaceae, such as E. coli is a main characteristic of gut inflammation and is related to multiple human diseases. However, how to control these E. coli overgrowth is not well understood. Here, we demonstrate that gut complement factor D (CFD) plays an important role in eliminating E. coli. Increased E. coli, which could stimulate inflammatory macrophages to induce colitis, were found in the gut of CFD deficient mice. We also showed that gut Reg4, which is expressed in gut epithelial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 62 publications
3
23
0
1
Order By: Relevance
“…In contrast to Reg III, Reg IV is produced predominantly by deep crypt secretory cells and intestinal enteroendocrine cells in the colon [55]. Gut Reg IV-and complement factor D-mediated membrane attack complexes may help to maintain gut homeostasis by elimination of inflammatory E. coli [56].…”
Section: Reg and Inflammatory Diseases (Gi Tract And Systemic Inflammation)mentioning
confidence: 99%
“…In contrast to Reg III, Reg IV is produced predominantly by deep crypt secretory cells and intestinal enteroendocrine cells in the colon [55]. Gut Reg IV-and complement factor D-mediated membrane attack complexes may help to maintain gut homeostasis by elimination of inflammatory E. coli [56].…”
Section: Reg and Inflammatory Diseases (Gi Tract And Systemic Inflammation)mentioning
confidence: 99%
“…In addition, enteropathogenic Escherichia coli also can activate NLRC4 21 . While equal amount of GFP-labeled Escherichia coli, which were isolated from DSS-mediated colitis and demonstrated to promote in ammation 27 , both LNCGM1082-/and NLRC4-/mice had also similarly increased bacteria as compared to wt mice in the feces after 2 days (Fig. 3i).…”
Section: Lncgm1082 Has Similar Effects With Nlrc4 On Regulating Maturation Of Il-1β and Pyroptosis Of Macrophagesmentioning
confidence: 99%
“…We previously reported that Reg4 could kill E. coli through complement-dependent pathway [35]. Since increased E. coli in colon are related to occurrence and development of multiple diseases such as obesity [36-38], we investigated the role of Reg4 in high-fat diet (HFD) mediated obesity using Reg4 knockout (KO) mice.…”
Section: Reg4 Promotes Resistance To High-fat Diet Induced Obesitymentioning
confidence: 99%
“…Reg4 associated gut microbiota/metabolites are related to IL-35 + cells Gut microbiota /metabolites play a critical role in the formation of immune system [1][2][3]. Reg4 can not only kill E. coli through complement-dependent pathway [35] but also induce damage to bacterial cell wall [33,34], implying that Reg4 might cause changed gut microbiota in gut. Indeed, ow cytometry showed that WGA + bacteria increased but LPS + bacteria reduced in the fresh stool of huREG4 IECtg mice; whereas WGA + bacteria decreased but LPS + bacteria increased in Reg4 KO mice as compared to their control (Fig.…”
Section: Reg4 Promotes Resistance To High-fat Diet Induced Obesitymentioning
confidence: 99%
See 1 more Smart Citation